2008
DOI: 10.5465/amr.2008.32465726
|View full text |Cite
|
Sign up to set email alerts
|

Corrupt Organizations or Organizations of Corrupt Individuals? Two Types of Organization-Level Corruption

Abstract: We focus on two fundamental dimensions of corruption in organizations: (1) whether the individual or the organization is the beneficiary of the corrupt activity and (2) whether the corrupt behavior is undertaken by an individual actor or by two or more actors. We use these dimensions to define a new conceptualization of corruption at the organization level: the organization of corrupt individuals. We contrast this conceptualization with the prevailing concept of organizational corruption and develop propositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
327
0
23

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(356 citation statements)
references
References 156 publications
(219 reference statements)
6
327
0
23
Order By: Relevance
“…As noted in Table 1, our review of the research on workplace crimes revealed that work on "organizational illegality," "corporate crimes," "unethical prosocial behaviors," and "corrupt organizations" (Baucus and Near 1991, Calavita et al 1997, Pinto et al 2008, Szwajkowski 1985, Umphress et al 2010) covers workplace crimes that are carried out with the intention to benefit the organization. For instance, organizational illegality is conceptualized as legally prohibited action that is taken by organizational members primarily on behalf of the organization (Szwajkowski 1985).…”
Section: Pro-organizational Workplace Crimementioning
confidence: 99%
See 3 more Smart Citations
“…As noted in Table 1, our review of the research on workplace crimes revealed that work on "organizational illegality," "corporate crimes," "unethical prosocial behaviors," and "corrupt organizations" (Baucus and Near 1991, Calavita et al 1997, Pinto et al 2008, Szwajkowski 1985, Umphress et al 2010) covers workplace crimes that are carried out with the intention to benefit the organization. For instance, organizational illegality is conceptualized as legally prohibited action that is taken by organizational members primarily on behalf of the organization (Szwajkowski 1985).…”
Section: Pro-organizational Workplace Crimementioning
confidence: 99%
“…Workplace crimes have often been studied on the basis of crimes committed (e.g., Ambrose et al 2002, Clinard and Quinney 1973, Greenberg 2002, individual or group involvement (e.g., Daboub et al 1995, Pinto et al 2008, Szwajkowski 1985, victims (e.g., Aquino and Bradfield 2000, Bennett and Robinson 2000, Warren 2003, organizational position (blue-collar versus white-collar) of the perpetrator (e.g., Aguilera and Vadera 2008, Clinard 1983, Sutherland 1940, as well as on the basis of crimes specific to a particular industry (Calavita et al 1997, Flannery andMay 2000).…”
Section: Typology Of Workplace Crimesmentioning
confidence: 99%
See 2 more Smart Citations
“…Corruption: Corruption is a central and unfortunate institutional issue in most developing countries such as those in Sub-Saharan Africa. Corruption is related to agency problems (Pinto et al 2008) and is therefore relevant when studying the relationship between ownership structure and board compensation. The corruption literature suggests that in the principal-agent model, the agent, in exchange for compensation or some sort of gain, has an incentive to favour a third party at the expense of the principal (Pinto et al 2008).…”
Section: Control Variablesmentioning
confidence: 99%